Prevalence and commonest predictors of gestational diabetes mellitus: a cross-sectional study - Nagalingam, Saranya; Murugaraj, Vaishnavi (International Journal of Advances in Medicine, 2019)
Background: Babies born to mothers with GDM are at increased risk of complications, primarily growth abnormalities and chemical imbalances such as hypoglycemia, GDM is a reversible condition and women who have adequate control of glucose level scan effectively decrease the associated risks and give birth to healthy babies. The objective was to estimate the prevalence and the predictors of gestational diabetes mellitus. Methods: This study was conducted as a cross sectional study among the antenatal mothers at the outpatient department of the rural and urban health centers of the KG hospital and PG institute and its affiliated centers in Coimbatore. The study period was one year and during which 150 antenatal mothers participated in the study. Results: The prevalence of GDM was 76 (9%) and 74 (11%) in rural and urban health centers respectively. The maximum number of GDM Mothers to be 26-30years of age with a peak indicating 42% and 39% of GDM mothers were found to be in primigravida, 48% of GDM mothers were primipara. About 65% of GDM pre-pregnant mothers were overweight according to BMI, 53% of GDM mothers had positive family history of DM. Majority of the study population 100 (67%) had HBA1C less than 6% and the remaining 50 (33%) had more than 6% value. The variables like age, gravida, parity, family history of diabetes, pre-pregnant BMI, history of PCOS, history of hypertension, history of hypothyroidism was compared with the glycaemic status (HBA1C values) and it was found to be statistically significant at P<0.05. Conclusions: The commonest risk factors which increases the incidence of GDM were family history of diabetes mellitus, overweight pre-pregnant BMI, history of PCOS, hypothyroidism, increasing gravidity and parity respectively.